The Effectiveness of a Counseling Program Based on the Mindfulness Approaches in Increasing the Psychological Well-Being among a Sample of Working Women at Al-Hassan Industrial Zone - Bany Ersheed, Esra; Al-Shreffen, Ahmad; Al-Refaei, Abeer (Dirasat: Educational Sciences, 2022)
Objectives: This study aims to discover the effectiveness of mindfulness therapy in enhancing the level of psychological well-being among a sample of working women in the Al-Hassan Industrial Zone in Irbid. The study sample consisted of 30 women working in the Al-Hassan Industrial Zone. They were randomly assigned to two equal groups: the experimental group and control group. Methods: To achieve the objectives of the study, the psychological well-being scale was used, in addition to a counseling program based on the mindfulness approach. This study used psychological well-being as a dependent variable and a descriptive-analytical approach was also used to analyze the data elicited from female students and women. It also relied on the mindfulness approach as an independent variable, the semi-experimental approach in revealing the impact of mindfulness on some variables for working women and students. Results: The results showed that there were statistically significant differences at the level of significance (α=0.05) between the two means of the pre and post-measurement of the level of psychological well-being according to the group in the post-test in favor of the experimental group. Also, the results of the following up exam comparisons among the members of the experimental group indicated that there were no statistically significant differences for the (T) test for the correlated samples of the psychological well-being scale and its dimensions. Conclusions: Depending on the results, it becomes clear that the counseling program was effective.